If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 = z + 13 Reorder the terms: 72 = 13 + z Solving 72 = 13 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 72 + -1z = 13 + z + -1z Combine like terms: z + -1z = 0 72 + -1z = 13 + 0 72 + -1z = 13 Add '-72' to each side of the equation. 72 + -72 + -1z = 13 + -72 Combine like terms: 72 + -72 = 0 0 + -1z = 13 + -72 -1z = 13 + -72 Combine like terms: 13 + -72 = -59 -1z = -59 Divide each side by '-1'. z = 59 Simplifying z = 59
| 5x+11+69+36=180 | | 2x2/3-4x=0 | | 3g+7.5=42 | | 65=g+33 | | 6.65=-4.75a | | 57+w=120 | | 58=p+31 | | e+15=19 | | 2y+21=3x-49 | | 8-4x+15=3x | | u+59=144 | | 6x+y+x+5y=180 | | 36x^8y^6/9x^2y | | k+44=101 | | -1/3(3x-6)=1-2x | | z+6=85 | | 102=v+53 | | -6r+3s-5r+8=0 | | 150=m+84 | | 35+b=86 | | 98=c+69 | | 9e+4=1+8e | | 85+d=99 | | 96+a=148 | | 1.5-x=-.5x | | 3n+5-n=0 | | 93=t+52 | | 8*n=16 | | s+21=66 | | 25+y=72 | | -22+x=-15 | | y+3z=20 |